Thinking in new boxes a new paradigm for business creativity - Brabandere, Luc de; Iny, Alan (New York Random House, 2013)
Outlines a new model of practical creativity that challenges business professionals to evaluate customers, goals, and companies in engaging alternative ways, explaining how to develop strategies for effective and adaptive business environments.
Keywords: Creative ability in business; Creative thinking; New products; Diffusion of innovations